Prioritizing Professional Values from the Viewpoint of Nurses of Shiraz University of Medical Sciences - Rostami, Khatereh; Khosravani , Mahboobeh; Mojab, Elaheh; Behzadi, Soudabeh (International Journal of Psychosocial Rehabilitation, 2020)
Background and aim: Nursing is an independent discipline and branch of the medical sciences whose mission is to provide the highest standard of health, care, medical and rehabilitation services and is the most important step in assessing the values of that organization. The aim of this study was to prioritize professional values from the perspective of nurses of Shiraz University of Medical Sciences. Methods: This descriptive-analytical study was performed in the hospitals of Shiraz University of Medical Sciences. The study population was all nurses with at least 5 years of work experience. The sampling method was simple random. Two questionnaires were used to assess nurses’ views on professional values. In the first part demographic information was reviewed and in the second part the revised questionnaire of nursing professional values was used. Results : In this study 113 nurses of Medical Sciences University participated .According to the total averages in each dimension, it was found that for nurses, "trust" is the most important and "pragmatism" is the least important. Conclusion: This evaluation provided useful information that could lead to more effective strategies and application of professional values in clinical practice.